2018
DOI: 10.1021/acs.jpclett.8b02982
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated and Non-Gaussian Diffusion of Cholesterol in Liquid Ordered Phase Bilayers Depends on the Flip-Flop and Spatial Arrangement of Cholesterol

Abstract: The diffusion of cholesterol in biological membranes is critical to cellular processes such as the formation of cholesterol-enriched domains. The cholesterol diffusion may be complicated especially when cholesterol flip-flops and/or stays at the membrane center. Understanding the diffusion mechanism of cholesterol at a molecular level should be, therefore, a topic of interest. We perform molecular dynamics simulations up to 100 μs for lipid bilayers with various concentrations of cholesterol. We find that chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…In this case of (σ np , ϕ, ϵ ij ) = (3σ, 6%, 1ϵ), the NP diffuses much longer distance during t = 100 than expected by the diffusion coefficient ( D ∥,np ). Such a non-Gaussian diffusion often indicates that the dynamics of NPs might be spatially heterogeneous. …”
Section: Resultsmentioning
confidence: 99%
“…In this case of (σ np , ϕ, ϵ ij ) = (3σ, 6%, 1ϵ), the NP diffuses much longer distance during t = 100 than expected by the diffusion coefficient ( D ∥,np ). Such a non-Gaussian diffusion often indicates that the dynamics of NPs might be spatially heterogeneous. …”
Section: Resultsmentioning
confidence: 99%
“…The short-time MSD of vesicle motion only marginally increases with time, because at this time scale, active motion of the MPM is negligible compared to the quasi-stationary thermal fluctuation of vesicle position with respect to the MPM. It is interesting to note that the short-time VDD has an exponential tail, a commonly observed feature of thermal motion in disordered fluids. The VDD along the microtubule becomes a power-law distribution after 0.5 s where the MPM’s active motion is the major contributor to vesicle displacement (Figure f–h).…”
mentioning
confidence: 96%
“…9−13 Coarse grain simulations suggested that cholesterol may enter the interleaflet space and produce domains by increasing membrane thickness that way. 13 This prediction, however, is not supported by any experimental evidence thus far. Hence, there is an impetus to perform ultrahigh spatial resolution morphological and spectroscopic mapping to identify the localization and distribution of cholesterol in lipid bilayers.…”
mentioning
confidence: 88%
“…Information on the spatial distribution of cholesterol within and between membrane domains is not accessible with bulk methods, and until recently, there have not been any microscopy methods to perform simultaneous morphological and chemical mapping on the nanometer scale. Computational studies were attempted to overcome this limitation. Coarse grain simulations suggested that cholesterol may enter the interleaflet space and produce domains by increasing membrane thickness that way . This prediction, however, is not supported by any experimental evidence thus far.…”
mentioning
confidence: 99%